2023
DOI: 10.3390/healthcare11142114
|View full text |Cite
|
Sign up to set email alerts
|

Are All Societies Ready for Digital Tools? Feasibility Study on the Use of Mobile Application in Polish Early Breast Cancer Patients Treated with Perioperative Chemotherapy

Grażyna Suchodolska,
Anna Koelmer,
Monika Puchowska
et al.

Abstract: Background: The population of individuals affected by breast cancer is growing, and with advances in cancer treatment implemented into usual care, there is an urgent need to improve the recognition, monitoring and treatment of therapy-induced adverse effects. This study aims to explore the use of an in-app electronic questionnaire to assess and monitor chemotherapy-related symptoms in early breast cancer patients treated with perioperative chemotherapy. Method: Between December 2019 and June 2021, 72 female st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Similarly, patients in this study reported that using a digital solution for collecting ePROMs would be acceptable as part of routine care. Previous evidence has shown that collecting PROMs in routine care could help bring key issues to the fore [15][16][17][45][46][47][48]. Furthermore, in this study, ePROMs were seen as potentially valuable in terms of contributing to the wider evidence base, as reported previously [47].…”
Section: Comparison With Other Worksupporting
confidence: 68%
See 1 more Smart Citation
“…Similarly, patients in this study reported that using a digital solution for collecting ePROMs would be acceptable as part of routine care. Previous evidence has shown that collecting PROMs in routine care could help bring key issues to the fore [15][16][17][45][46][47][48]. Furthermore, in this study, ePROMs were seen as potentially valuable in terms of contributing to the wider evidence base, as reported previously [47].…”
Section: Comparison With Other Worksupporting
confidence: 68%
“…Nevertheless, this did not appear to impact the perceived usefulness of the clinician dashboard. Second, patients' age was suggested as a possible barrier to use by some clinicians, as articulated in previous studies [17,20,46,48]. However, despite suggesting changes relating to the accessibility of the app, other clinicians as well as patients (median age of 67 years) indicated they would use the technology and did not report age as a barrier.…”
Section: Comparison With Other Workmentioning
confidence: 93%
“…Certainly, some tools offer unique capabilities in branching logic to eliminate unnecessary questions and optimize the experience for the user. 32 , 33 However, our results show that only a minority use digital tools in assessing mucositis, citing the lack of universally accepted tools as the main barrier (39% of respondents), followed by cost (23%), lack of appropriate infrastructure (22%), lack of literature (20%), patient hesitancy (15%) and time (12%). This is not surprising, as not every medical community is prepared for advanced digital tools and parameters such as the patient's age/technical literacy should be carefully taken into consideration.…”
Section: Discussionmentioning
confidence: 85%
“…This is not surprising, as not every medical community is prepared for advanced digital tools and parameters such as the patient's age/technical literacy should be carefully taken into consideration. 32 However, patients that use digital health tools can become more independent, proactive and accepting of themselves. 33 Further research is needed to explore the added benefit of digital tools in assessing mucositis, and societal leadership is needed to identify the desirable attributes of such platforms both in their design, development and implementation.…”
Section: Discussionmentioning
confidence: 99%